Superconducting HfO2-added solution-derived YBa2Cu3O7 nanocomposite films: the effect of colloidal nanocrystal shape and crystallinity on pinning mechanism. (1st August 2022) - Rijckaert, H; Malmivirta, M; Banerjee, S; Billinge, S J L; Huhtinen, H; Paturi, P; De Buysser, K; Van Driessche, I
Abstract: Two different types of monoclinic HfO2 nanocrystals were employed in this work to study the effect of nanocrystal shape and crystallinity on the structural defects in the YBa2Cu3O7−δ (YBCO) matrix as it leads to an enhancement of pinning performances of solution-derived YBCO nanocomposite films. In this work the nanorod-like HfO2 nanocrystals obtained from surfactant-controlled synthesis led to short intergrowths surrounding the particles, while spherical HfO2 nanocrystals from the solvent-controlled synthesis led to the formation of long stacking faults in the YBCO matrix. It means that the small difference in crystallinity, lattice parameters, nanocrystal structures, core diameter of preformed nanocrystals in colloidal solutions have a strong influence on the formation of the structural defects around the particles in the YBCO matrix, leading to different pinning performances.